2004
DOI: 10.1242/dev.00961
|View full text |Cite
|
Sign up to set email alerts
|

The deafness genedfna5is crucial forugdhexpression and HA production in the developing ear in zebrafish

Abstract: Over 30 genes responsible for human hereditary hearing loss have been identified during the last 10 years. The proteins encoded by these genes play roles in a diverse set of cellular functions ranging from transcriptional regulation to K+ recycling. In a few cases, the genes are novel and do not give much insight into the cellular or molecular cause for the hearing loss. Among these poorly understood deafness genes is DFNA5. How the truncation of the encoded protein DFNA5 leads to an autosomal dominant form of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 42 publications
5
56
0
Order By: Relevance
“…The latter could be explained by the fact that when apoptotic pathways are downregulated, DNA repair mechanisms need to be upregulated to maintain viable conditions. Interestingly, genes involved in cartilage maintenance were also upregulated in Dfna5 KO mice, linking our findings to those obtained by Busch-Nentwich et al 22 They found that zebrafish injected with Dfna5 morpholino's displayed an absent expression of Ugdh (UDPglucose dehydrogenase), leading to reduced production of hyaluronic acid, resulting in impaired facial cartilage differentiation. As Dfna5 KO mice do not display this phenotype, it is possible that the gene sets involved in cartilage development provide compensatory mechanisms resulting in the lack of phenotype in these mice.…”
Section: Discussionsupporting
confidence: 89%
“…The latter could be explained by the fact that when apoptotic pathways are downregulated, DNA repair mechanisms need to be upregulated to maintain viable conditions. Interestingly, genes involved in cartilage maintenance were also upregulated in Dfna5 KO mice, linking our findings to those obtained by Busch-Nentwich et al 22 They found that zebrafish injected with Dfna5 morpholino's displayed an absent expression of Ugdh (UDPglucose dehydrogenase), leading to reduced production of hyaluronic acid, resulting in impaired facial cartilage differentiation. As Dfna5 KO mice do not display this phenotype, it is possible that the gene sets involved in cartilage development provide compensatory mechanisms resulting in the lack of phenotype in these mice.…”
Section: Discussionsupporting
confidence: 89%
“…3F,G). Expression of the semicircular canal tissue markers ugdh1 (Busch-Nentwich et al, 2004) and dacha (Hammond et al, 2002) is, however, normal in the epithelial projections that are present (data not shown). The otoliths remain very small and sit close to one another in the mutant (Fig.…”
Section: Otic Vesicle Morphology Is Abnormal In Sox10 Mutantsmentioning
confidence: 90%
“…The early development of the zebrafish inner ear is similar to that of other vertebrates (Bang et al, 2001;Whitfield et al, 2002;Riley and Phillips, 2003) and its sensory hair cells are homologous to those found in mammals (Coffin et al, 2004). Over 50 genes are known to impact the zebrafish auditory inner ear and/or vestibular system Whitfield et al, 1996;Whitfield et al, 2002;Riley and Phillips, 2003;Starr et al, 2004;Nicolson, 2005) and many of these genes are conserved and affect the inner ear development and function in other vertebrates, including humans (Nicolson et al, 1998;Moorman et al, 1999;Riley and Moorman, 2000;Busch-Nentwich et al, 2004;Kappler et al, 2004;Kozlowski et al, 2005). However, unlike mammals, zebrafish develop from eggs ex utero and are transparent during the first few weeks of life.…”
Section: Introductionmentioning
confidence: 95%